Про теплові потоки в елементах дискових гальм - Осташук, Микола (ТзОВ «Галицька видавнича спілка», 2021)
The influence of various factors on the distribution of heat fluxes in the elements of disc brakes has been studied. The identified factors can be used in the design of brake mechanisms.
About heat flows in disc brake elements
Keywords: 656.13